Changes in the Sources of Olivine-Tempered Ceramics and Social Interaction Patterns in the Virgin Branch Region. Issue 4 (2nd October 2019) - Sakai, Sachiko
Abstract : Olivine-tempered ceramics are widely distributed in the Virgin Branch Puebloan region. The sources of olivine are in the highlands near Mt. Trumbull and Tuweep. Thus, the presence of olivine-tempered ceramics in the lowland Virgin area indicates economic and social ties between the highland and lowland populations. The ceramic compositional study using LA-ICP-MS suggests that these olivine-tempered ceramics were produced not only in Mt. Trumbull but also in the lowland Virgin area. The study also suggests that some of the olivine-tempered ceramics made in the lowland Virgin area were moved back to Mt. Trumbull. In this study, I explore the mechanisms of social interactions that moved olivine-tempered ceramics within various areas. In particular, I address the question of whether these olivine-tempered ceramics were transported as a result of trading or human migrations during various time periods. To answer this question, ceramic compositional data are combined with optically stimulated luminescence (OSL) dating.